Modeling, analysis, and optimization of process and energy systems - Knopf, F. Carl, 1952- (Hoboken, N.J. : John Wiley & Sons, 2012)
'Energy costs impact the profitability of virtually all industrial processes. Stressing how plants use power, and how that power is actually generated, this book provides a clear and simple way to understand the energy usage in various processes, as well as methods for optimizing these processes using practical hands-on simulations and a unique approach that details solved problems utilizing actual plant data. Invaluable information offers a complete energy-saving approach essential for both the chemical and mechanical engineering curricula, as well as for practicing engineers'--
Includes bibliographical references and index.
Keywords: Factories -- Energy conservation; Manufacturing industries -- Energy conservation; Industrial efficiency -- Simulation methods; Manufacturing processes -- Evaluation; Electric power-plants -- Efficiency